2019
DOI: 10.1210/jc.2018-02318
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in Primary vs Secondary School Children With Obesity and Responsiveness to Lifestyle Intervention

Abstract: Context Childhood obesity increases the risk of diseases as diabetes, cardiovascular disease, and nonalcoholic fatty liver disease. Objective To evaluate the prevalence of comorbidities in school-age children with obesity and to compare its prevalence and the effect of a lifestyle intervention between children in primary and secondary school and between boys and girls. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
0
20
0
2
Order By: Relevance
“…These findings from our study and the above-mentioned stud- the future economic burden of this disease on society. [17][18][19] In conclusion, the results of this study suggest screening for NAFLD in children with obesity in the Netherlands is widely performed but in highly variable way. This emphasises the need to come to one comprehensive and easy to apply screening strategy on international and national level.…”
Section: Screening Based On Which Guideline? N (%)mentioning
confidence: 72%
See 1 more Smart Citation
“…These findings from our study and the above-mentioned stud- the future economic burden of this disease on society. [17][18][19] In conclusion, the results of this study suggest screening for NAFLD in children with obesity in the Netherlands is widely performed but in highly variable way. This emphasises the need to come to one comprehensive and easy to apply screening strategy on international and national level.…”
Section: Screening Based On Which Guideline? N (%)mentioning
confidence: 72%
“…Local guideline for obesity in children 5 (19) International guideline 0 (0) 13 Arguments favouring and opposing screening are presented in Table 3. Indications for NAFLD screening the US also lack a comprehensive approach.…”
Section: Screening Based On Which Guideline? N (%)mentioning
confidence: 99%
“…Additionally, the negative association between PA and age highlights the importance of early PA promotion since the presence of comorbidities is already evident in primary school children with obesity 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a chronic disease associated with several comorbidities including Type 2 diabetes (T2D), cardiovascular disease (including hypertension and dyslipidemia), musculoskeletal disorders and some cancers [4]. Correlated to the increase in prevalence of childhood obesity, an alarming shift in the onset of these obesity related comorbidities towards childhood has been noted, particularly for T2D [1,[5][6][7][8][9][10]. The timeframe between the onset of T2D and the requirement of insulin therapy is shorter in adolescents than in adults, with medical treatments failing earlier [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The timeframe between the onset of T2D and the requirement of insulin therapy is shorter in adolescents than in adults, with medical treatments failing earlier [7,8]. Additionally, other comorbidities including metabolic disturbances also develop earlier in life [10]. All these factors contribute to a poor prognosis in adolescents with severe obesity, in whom studies have indicated a reduction in life expectancy of almost 20 years [5,11,12].…”
Section: Introductionmentioning
confidence: 99%